The Performance of Malaysian Initial Public Offerings During the Financial Crisis of July 1997 - Jaafar Sidik, Morni Hayati (2000)
This study examines the performance of IPOs in Malaysia during the economic crisis between July 1997 to September 1999. Using the same methodology as previous studies on IPOs, this study investigates the performance of new issues both in the short run and long run based on a sample of 81 newly listed companies on the KLSE. The overall results provide evidence consistent with previous studies that most IPOs are, generally, underpriced on their first day of trading. This study documented an average first day return of 37.12%, a value significantly lower than the earlier studies on the KLSE. Comparing Main Board (MB) and Second Board (SB) IPOs performances, the results indicate that firms listed on the SB provide higher returns than firms listed on MB. This study documented two important findings when a short run performance (from week one to month six) is analysed. Firstly, when investors are fortunate to be allocated with new issues at the offering price, they are able to gain some positive returns but at a rate lower than that observed during the first day. Secondly, if they purchased the new issues at the aftermarket price, investors will earn negative returns. In the long run (12 months), IPOs is an unfavourable investment if the shares are bought at the aftermarket price. This result seems to contradict with findings of previous studies in Malaysia. A strategy of investing IPOs at their offering price and held them for one year would left the investor with some positive returns.